IMPLEMENTASI PENJAMIN MUTU INTERNAL DAN EKSTERNAL DALAM PENDIDIKAN DASAR DI SDN 1 JEROWARU TAHUN 2021 - Ahmad Dedi Marzuki (LPPM Institut Pendidikan Nusantara Global, 2021)
The purpose of this study is to investigate what affects the quality of education, one of the determining factors is quality assurance both internally and externally in educational institutions because educational institutions have a very central position in printing the nation's next generations, for that the role of educational institutions here In addition to being one of the mediators in producing the nation's generation, the success of the institution also cannot be separated from several aspects that support the institution to become a quality institution, such as the role of society, the role of parents of students, the government, students who are external aspects of the institution, while the internal aspects are here. which includes the organization of these institutions, such as school principals, teachers, staff (office boys) cleaning service, janitorial waiters and other components.